Postoperative clinical outcome and complications of combined cannulated cancellous screw with Kirschner wire in adolescent femoral neck fractures - Kenmegne, Guy Romeo; Zou, Chang; Lin, Yixiang; Yin, Yijie; Huang, Shengbo; Fang, Yue (Frontiers in Pediatrics, 2023)
Abstract Purpose: The fractures of femoral neck account for less than 1% of paediatric and adolescent fractures. Due to the high incidence of complications, and the age of the patients, the choice of fixation approach remains controversial among orthopaedic surgeons. This study aimed to evaluate the postoperative outcomes and complications of femoral neck fracture in adolescents with open physis, following transphyseal fixation using a combined Cannulated Cancellous Screw and Kirshner wire fixation. Methods: Data of 19 patients all between 12-19 years from January 2010 to January 2021 were retrospectively studied. The follow-up period was 1 to 11 years (5.83±3.76 years).The variables of interest including demographic and clinical variables (Age, BMI, gender, side of injury, fracture classification, operation time, time to surgery and LOS), postoperative outcomes and complications (fracture healing time, non-union, coxa vara, osteoarthritis, avascular necrosis, screw loosening, femoral shortening), were analysed. The assessment of the hip function was done on final follow-up using the Ratliff scoring system. Results: There was a male predominance 76%; the mean age was 16.14±1.57 years and the most frequent mechanism of injury was the fall from height. Debelt type II and III were the most encountered. The mean intraoperative time was 54.71±7.85 minutes, the length of hospital stay (LOS) was 8.34±1.81days and the time to surgery was 2.60±1.16 days; the fracture healing time was 3.31±1.04 months. The postoperative complications encountered were coxa vara osteoarthritis, spontaneous dislocation and neck shortening. The Clinical assessment revealed good result in 89% of patients and fair in 11 % of patients. Conclusion: The transphyseal fixation using cannulated cancellous screw combined with Kirshner wire in our patients provided acceptable results. Thus, this approach can be a viable alternative in management of adolescent femoral neck fracture with open physis.